Double-ion-doped phosphate sodium-ion battery positive electrode active material and preparation method thereof, positive electrode material and sodium-ion battery
By introducing dual-ion doping technology into the positive electrode material of sodium ion battery, complexing using a metal manganese chromium source and an organic chelating agent, and combining in-situ doping of metal magnesium and zirconium sources, the limitations of existing materials in electron exchange and sodium ion diffusion kinetics are solved, and higher specific capacity and magnification performance are achieved.
Patent Information
- Application Number
- CN202411665242.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
AI Technical Summary
The existing sodium ion battery positive electrode materials have limitations in electron exchange and sodium ion diffusion kinetics, resulting in insufficient specific capacity and rate performance.
The two-ion-doped phosphate-based sodium electropositive electrode material is used to optimize the structure and performance of the material by introducing a metal manganese chromium source and an organic chelating agent.
It improves the kinetic performance and rate performance of the material, enhances the crystal structure stability, optimizes the migration rate of sodium ions, and improves the cycling performance and voltage platform of the material.
Smart Images

Figure CN119569016A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery positive electrode materials, and in particular to a double-ion doped phosphate-based sodium positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Sodium ion battery is also a kind of "rocking chair battery". The working principle of sodium ion battery is basically the same as that of lithium ion battery. It also uses the reversible directional migration process of alkali metal ions between positive and negative electrodes to realize the charging and discharging of the battery. During charging, Na+ escapes from the positive electrode material, passes through the diaphragm through the electrolyte and embeds into the negative electrode material. The discharge process is the opposite. During the charging and discharging process, the same number of electrons are transferred through the external circuit and migrate between the positive and negative electrode materials together with Na+ to maintain charge balance. x MO2 is the positive electrode material and hard carbon is the negative electrode material.
[0003] The positive electrode material is the key to the energy density of sodium-ion batteries. Polyanionic compounds have the advantages of high safety and long cycle due to their higher operating voltage and stable three-dimensional structural framework.
[0004] The types of polyanion groups include orthophosphate, pyrophosphate, sulfate, mixed polyanion, fluorophosphate / sulfate, silicate and molybdate, among which orthophosphate is the current mainstream process route. This type of material has the following advantages: 1) The three-dimensional framework structure composed of strong PO covalent bonds makes the material highly stable and safe; 2) Orthophosphate materials generally contain multiple Na + , and transition metal ions have multiple intermediate valence states, and multiple electron transfers can achieve higher specific capacity; 3) The inductive effect of the polyanion group weakens the MO bond, which improves the redox potential of the transition metal ions, thereby showing good cycle stability, thermal stability and excellent safety. However, since the polyhedron composed of transition metals and oxygen atoms in the orthophosphate material is blocked by the anion tetrahedron, the electron cloud of the transition metal is in a discontinuous state, which hinders the electron exchange. The lack of electron transport pathways leads to low conductivity and slow sodium ion diffusion kinetics, which limits the specific capacity and rate performance of sodium ion batteries. Based on the above problems, improving the material platform voltage and increasing the ionic conductivity are of great significance to the development of orthophosphate materials.
[0005] In the prior art, for example, the invention patent CN 115207347A introduces metal titanium doping to replace part of the vanadium position to obtain a titanium-doped sodium vanadium manganese phosphate positive electrode material, which effectively improves its cycle performance and rate performance, but the vanadium element itself is harmful and poses a safety and environmental hazard; the invention patent CN 113422034A uses metal magnesium or aluminum ions to dope and modify the iron-based polyanion compound positive electrode material, which increases the lattice spacing to a certain extent, widens the migration channel of sodium ions, and optimizes the kinetic properties of the material, but due to the limited voltage platform of the iron-based type, the energy density of its battery is insufficient; the invention patent CN 115132981A obtains a fluorine-containing iron-based phosphate positive electrode material by using binary doping synergistic polysaccharides and imidazoline surfactants as a composite carbon source. The material has a high reversible specific capacity, and the uniform and dense carbon coating layer on its surface significantly improves the cycle stability. Because the complexation effect between different metal ions is not considered, the narrow voltage window (only 2.5-4.0V) is limited to avoid the dissolution of metal elements.
[0006] In view of this, it is necessary to provide a new sodium battery positive electrode material to improve the above-mentioned technical problems. Summary of the invention
[0007] The main purpose of the present invention is to provide a double-ion doped phosphate-based sodium positive electrode material and a preparation method, a sodium ion battery and its application, so as to solve the above-mentioned technical problems.
[0008] To achieve the above object, the present invention provides a method for preparing a double-ion doped phosphate sodium positive electrode active material, comprising the steps of:
[0009] S1, taking a sodium source, a manganese source, a magnesium source, a chromium source, a zirconium source and a phosphorus source according to a stoichiometric ratio of 3.8-4.2: 0.7-0.95: 0.05-0.3: 0.7-0.95: 0.05-0.3: 1; using an organic chelating agent in an amount of 1.0-8.0% of the total mass of the metallic manganese and chromium sources;
[0010] S2, mixing the metal manganese chromium source and the chelating agent in a solvent, dissolving them into a solution A according to a solid mass fraction of 20% to 60%;
[0011] S3, mixing a phosphorus source, a sodium source, a magnesium source and a zirconium source in a solvent, dissolving them into a solution B according to a solid mass fraction of 5% to 30%, mixing the solution B with the solution A while continuing to stir at a constant temperature, and obtaining a solid phase precursor material through high temperature spray drying;
[0012] S4, sintering the precursor material at a high temperature of 350-750° C. for 6-24 hours, cooling it to room temperature and then crushing it to obtain a double-ion doped phosphate-based sodium positive electrode material.
[0013] Further, the sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium phosphate, sodium dihydrogen phosphate, sodium citrate, sodium alginate, sodium hydroxide, sodium acetate or sodium oxalate;
[0014] The manganese source is one or more of manganese acetate, manganese oxalate, manganese carbonate, manganese nitrate, manganese stearate and manganese phosphate;
[0015] The magnesium source is selected from at least one of magnesium nitrate, magnesium acetate, magnesium citrate and magnesium oxalate;
[0016] The chromium source is selected from one or more of chromium phosphate, chromium acetate, chromium nitrate or sodium chromate;
[0017] The zirconium source is selected from at least one of zirconium acetate, zirconium nitrate, zirconium carbonate and zirconium hydrogen phosphate;
[0018] The phosphorus source is selected from at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium monohydrogen phosphate or sodium dihydrogen phosphate;
[0019] The organic chelating agent is selected from at least one of ethylenediaminetetraacetic acid, citric acid, tartaric acid, ascorbic acid and oxalic acid;
[0020] The solvent is selected from at least one of anhydrous ethanol and deionized water.
[0021] Furthermore, in the step S2, solution A is prepared by stirring and dissolving at a constant temperature of 80 to 130° C.; and in the step S3, solution B is prepared by stirring and dissolving at a constant temperature of 80 to 130° C.
[0022] Furthermore, the solvent includes at least one of ethanol or water.
[0023] Furthermore, in step S4, the precursor material is transferred to nitrogen and heated to 350-750°C at a heating rate of 2-20°C / min for high temperature sintering for 6-24h.
[0024] The present invention also provides a double-ion doped phosphate-based sodium positive electrode active material, which is prepared by the preparation method of the double-ion doped phosphate-based sodium positive electrode active material as described in any one of the above items.
[0025] The present invention also provides a double-ion doped phosphate sodium positive electrode material, comprising the double-ion doped phosphate sodium positive electrode active material as described above, a conductive agent and a binder.
[0026] Furthermore, the conductive agent includes conductive carbon black, and the adhesive includes PVDF.
[0027] The present invention also provides a dual-ion doped sodium phosphate positive electrode plate, comprising a current collector and a positive electrode coating coated on the current collector, wherein the positive electrode coating is formed by coating a slurry made of the dual-ion doped sodium phosphate positive electrode material as described above and an NMP solvent with a solid content of 40% to 80% on the current collector and drying it.
[0028] The present invention also provides a sodium ion battery, comprising the double-ion doped phosphate-based sodium battery positive electrode plate as described above.
[0029] The present invention also provides an application of the double-ion doped phosphate-based sodium battery positive electrode plate as a sodium ion battery positive electrode.
[0030] The present invention provides a double-ion doped phosphate-based sodium positive electrode material and a preparation method, a sodium ion battery and its application. By introducing an organic chelating agent that adds 1.0 to 8.0% of the total mass of a metal manganese-chromium source, a metal ion complexing effect is achieved to prevent metal dissolution during the sodium extraction process, and a soluble metal salt (manganese-chromium source) is dissolved to prepare nanoparticles with uniform and stable phases, small and concentrated grain sizes (about 50 to 500 nm). The nanometer size can shorten the migration path of ions, reduce the polarization internal resistance of the material, and is beneficial to the kinetic performance of the material. A metal magnesium source, a metal zirconium source and a chelating agent are then introduced to in-situ dope the material, wherein metal magnesium and metal zirconium are doping elements, and metal magnesium occupying the manganese position can enhance the stability of the crystal structure and alleviate the adverse effects of manganese elements due to the Jan-Taylor effect; metal zirconium occupying the chromium position can induce lattice distortion and produce defects, thereby optimizing the migration rate of sodium ions, improving the rate performance of the material, and improving the rate performance and cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:
[0032] Figure 1 It is a schematic flow chart of the preparation method of the double-ion doped phosphate sodium positive electrode material in the present invention.
[0033] Figure 2 This is the XRD diagram of the double-ion doped phosphate sodium cathode material in Example 1 of the present invention.
[0034] Figure 3 This is a SEM image of the double-ion doped phosphate sodium cathode material in Example 1 of the present invention.
[0035] Figure 4 This is a discharge cycle curve diagram of the double-ion doped phosphate sodium cathode material in Example 1 of the present invention.
[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0037] The following is a clear and complete description of the technical problems solved by the embodiments of the present invention, the technical solutions adopted, and the technical effects achieved in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other equivalent or obviously modified embodiments obtained by ordinary technicians in this field without creative work fall within the scope of protection of the present invention. The embodiments of the present invention can be concretized in a variety of different ways as defined and covered in the claims.
[0038] It should be noted that in the following description, many specific details are given for ease of understanding, but it is obvious that the present invention can be implemented without these specific details.
[0039] It should be noted that, in the absence of clear limitation or conflict, the various embodiments of the present invention and the technical features therein can be combined with each other to form a technical solution.
[0040] The preparation experiment of the double ion doped phosphate sodium positive electrode active material provided in the present application includes Examples 1-5 and Comparative Examples 1-3, and the specific process parameters are shown in Table 1. The process method is as follows Figure 1 shown.
[0041] Table 1 Process parameters of Examples 1-5 and Comparative Examples 1-3
[0042]
[0043] The specific electrical performance test is performed according to the following process steps:
[0044] The double-ion-doped phosphate-based sodium positive electrode active materials prepared in Examples 1-5 and Comparative Examples 1-3 were assembled into sodium ion button cells for electrochemical characterization:
[0045] The prepared phosphate material was used as the positive electrode active material and mixed with conductive carbon black (Carbon Black) and conductive binder PVDF in a vacuum degassing machine at a mass ratio of 8:1:1 for 60 minutes. N-methylpyrrolidone (NMP) was used as a solvent to control the solid content of the mixture to 40-80%. The mixed slurry was then evenly coated on a metal aluminum foil, transferred to 80°C for vacuum drying for 6 hours, and cut into small discs with a diameter of 14 mm after cooling. The weighed positive small discs were placed in a glove box for standby use, and the CR2032 button battery was assembled in the order of placing the negative electrode shell, metal sodium, diaphragm, positive electrode sheet, gasket, spring sheet, and positive electrode shell. The diaphragm used a PP / PE composite diaphragm, and the electrolyte used a 1.0M sodium perchlorate (NaClO4) solution of propylene carbonate (PC) containing 3% fluoroethylene carbonate (FEC), and the electrolyte addition amount was 120μL. After assembly, the package was left to stand for 6 hours, and the assembled battery was tested for charge and discharge (1C = 160mAh / g) at room temperature (25°C) in the voltage range of 1.4-4.5V using the Shenzhen Xinwei test system. The battery, which had been activated by 0.1C cycles for one week, was then charged / discharged at 0.1C with an interval of 30 minutes, and then left to stand for 120 minutes to allow the voltage to reach equilibrium. According to the simplified equation, the sodium ion migration rate D was calculated. Na The value is as follows:
[0046]
[0047] Where τ is the duration of the current pulse (in seconds, s), m B The mass of active substance (in grams, g), M B is the molecular weight (in grams per mole, g / mol), V M is the molar volume (in cubic centimeters per mole, cm 3 / mol), A is the total contact area between the electrode and the electrolyte (in square centimeters, cm 2 ), ΔE S The difference is the interval time between two consecutive stable voltages (in seconds, s), ΔE τ The potential difference between the equilibrium potential (in volts, V), the potential maximum current pulse, and L is the thickness of the electrode (in millimeters, mm).
[0048] The electrical performance test results are shown in Table 2.
[0049] Table 2 Comparison of test data of Examples 1-5 and Comparative Examples 1-3
[0050]
[0051]
[0052] Please combine Figure 2-Figure 4 The XRD refinement diagram shows that the material prepared by the present invention has high crystallinity and high purity without other impurities. SEM shows that the material presents a clear single crystal morphology, and the overall dispersion of the material is good. The particle size is about 50-400nm, and the distribution of large and small particles is conducive to the compaction density of the material. According to the charge and discharge curve diagram and Table 2, it can be seen that the voltage platform of the material is relatively high (3.7V is 4.2V is ), and its irreversible capacity loss is small (the first efficiency is as high as 96.32%).
[0053] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a double-ion doped phosphate sodium positive electrode active material, characterized in that: Includes steps: S1, taking a sodium source, a manganese source, a magnesium source, a chromium source, a zirconium source and a phosphorus source according to a stoichiometric ratio of 3.8-4.2: 0.7-0.95: 0.05-0.3: 0.7-0.95: 0.05-0.3: 1; using an organic chelating agent in an amount of 1.0-8.0% of the total mass of the metallic manganese and chromium sources; S2, mixing the metal manganese chromium source and the chelating agent in a solvent, dissolving them into a solution A according to a solid mass fraction of 20% to 60%; S3, mixing a phosphorus source, a sodium source, a magnesium source and a zirconium source in a solvent, dissolving them into a solution B according to a solid mass fraction of 5% to 30%, mixing the solution B with the solution A while continuing to stir at a constant temperature, and obtaining a solid phase precursor material through high temperature spray drying; S4, sintering the precursor material at a high temperature of 350-750° C. for 6-24 hours, cooling it to room temperature and then crushing it to obtain a double-ion doped phosphate-based sodium positive electrode material.
2. The method for preparing the double-ion doped phosphate sodium positive electrode active material according to claim 1, characterized in that: The sodium source is selected from at least one of sodium carbonate, sodium bicarbonate, sodium phosphate, sodium dihydrogen phosphate, sodium citrate, sodium alginate, sodium hydroxide, sodium acetate or sodium oxalate; The manganese source is one or more of manganese acetate, manganese oxalate, manganese carbonate, manganese nitrate, manganese stearate and manganese phosphate; The magnesium source is selected from at least one of magnesium nitrate, magnesium acetate, magnesium citrate and magnesium oxalate; The chromium source is selected from one or more of chromium phosphate, chromium acetate, chromium nitrate or sodium chromate; The zirconium source is selected from at least one of zirconium acetate, zirconium nitrate, zirconium carbonate and zirconium hydrogen phosphate; The phosphorus source is selected from at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium monohydrogen phosphate or sodium dihydrogen phosphate; The organic chelating agent is selected from at least one of ethylenediaminetetraacetic acid, citric acid, tartaric acid, ascorbic acid and oxalic acid; The solvent is selected from at least one of anhydrous ethanol and deionized water.
3. The method for preparing the double-ion doped phosphate sodium positive electrode active material according to claim 1, characterized in that: In the step S2, solution A is prepared by stirring and dissolving at a constant temperature of 80 to 130° C.; and in the step S3, solution B is prepared by stirring and dissolving at a constant temperature of 80 to 130° C.
4. The method for preparing the double-ion doped phosphate sodium positive electrode active material according to claim 1, characterized in that: In the step S4, the precursor material is transferred to nitrogen and heated to 350-750° C. at a heating rate of 2-20° C. / min for high-temperature sintering for 6-24 hours.
5. A double-ion doped phosphate-based sodium positive electrode active material, characterized in that: The material is prepared by the method for preparing a double-ion-doped phosphate-based sodium positive electrode active material as described in any one of claims 1 to 4.
6. A double-ion doped phosphate sodium positive electrode material, characterized in that: It comprises the double-ion doped phosphate sodium positive electrode active material as described in claim 5, a conductive agent and a binder.
7. A double-ion doped phosphate sodium positive electrode material according to claim 6, characterized in that: The conductive agent includes conductive carbon black, and the binder includes PVDF.
8. A double-ion doped phosphate sodium battery positive electrode plate, characterized in that: It includes a current collector and a positive electrode coating coated on the current collector, wherein the positive electrode coating is formed by coating a slurry made of a double-ion-doped phosphate sodium positive electrode material as described in claim 6 or 7 and an NMP solvent with a solid content of 40% to 80% on the current collector and drying it.
9. A sodium ion battery, characterized in that: It comprises the double-ion doped phosphate sodium positive electrode plate as described in claim 8.
10. Use of the dual-ion doped phosphate sodium battery positive electrode sheet as claimed in claim 8 as a positive electrode for a sodium ion battery.
Citation Information
Patent Citations
Binary doped iron-based fluorophosphate sodium ion positive electrode material and preparation method thereof
CN115132981A
Preparation and application method of ion-doped phosphate positive electrode material
CN114408892A
Ternary polyanionic phosphate sodium ion battery positive electrode material and preparation method thereof
CN116864675A
Lithium ion cell top cover
CN117937064A
Phosphate silicate material with olivine crystallographic structure
EP3492427A1